Utilization of Waste Fat from Catfish (Pangasius) in Methyl Esters Preparation Using Cao Derived from Waste Marine Barnacle and Bivalve Clam as Solid Catalysts - Gaanty Pragas, Maniam; Noor, Hindryawati; Irma, Nurfitri; Intan Shafinaz, Abd Manaf; Neshabran, Ramachandran; Mohd Hasbi, Ab. Rahim (Elsevier Ltd, 2015)
The use of waste oils/fats, as well as catalyst from waste materials, for producing methyl esters (biodiesel) via transesterification has been research of recent interest. In the present work, the transesterification of waste catfish fat using barnacle and bivalve clam as a heterogeneous catalyst was attempted. X-ray diffraction and FTIR results show that, upon thermal activation, both shells transformed into CaO, the active ingredient that catalyzes the reaction. In addition, the results showed that the methyl esters (ME) content of reaction catalyzed by barnacle and bivalve clam were at 97.6 ± 0.03 and 92.0 ± 0.05%, respectively in 3 h reaction duration at 65 °C. Optimization of reaction parameters revealed that MeOH:oi at 12:1 (molar) and catalyst at 4 wt.% as an optimal reaction conditions for both catalysts. Furthermore, the catalysts can be reused for four cycles while maintaining ME content above 90%.